Promoting Islamic Social Finance: Experience From Amanah Ikhtiar Malaysia - Zainol, Zairy (2018)
The absence of a comprehensive study limits the understanding of the factors that can catalyze the success of the AIM microcredit scheme to help the poor. The results of the past study have shown the effectiveness of micro credit schemes in terms of increasing the income of Amanah Ikhtiar Malaysia (AIM) Sahabat. In addition to measuring the effectiveness of these financing schemes in the broader scope, there must also be an action plan that ensures the sustainability of the AIM microcredit financing model. Based on the problem statement discussed, this study tries to look at the impact of the financing given by AIM in promoting Islamic social finance, particularly on the improvement of Sahabat standard of living over the duration of their participation with AIM. The research data are primary and secondary data. Primary data refers to data obtained through questionnaires, while secondary data refers to data from the AIM Branch. The data were tabulated and used descriptive analysis (frequency, mean, median, minimum and maximum), cross-tabulation and statistical test. Generally, there is an increase in project income and Sahabat households income comparing before and after participating in the AIM scheme. Sahabat projects’ performance is seen to be excellent at the early stage of participation. Therefore, the Islamic social finance through the role played by AIM has a good impact to the socioeconomic of the society